Sosialisasi dan Pelatihan Penggunaan Absensi Berbasis Mobile di SMA Negeri 21 Bandung - Murnawan, Murnawan; Sapanji, R.A.E. Virgana Targa; Lestari, Sri; Rosalin Samihardjo (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: The purpose of this activity is to provide training and guidance on the use of a mobile-based attendance system using QR-Codes and geofence to improve efficiency in attendance management and data security. Method: The training and socialization process involved several steps, including identifying the application features, creating training materials, conducting internal testing, introducing the concept to teachers and students, demonstrating the application's usage, and providing practical training sessions. The training used interactive lectures, demonstrations, and hands-on practice to ensure participants understood and could use the mobile attendance application effectively. Results: Socialization and training received positive responses. For teachers, 91% found the training excellent, and 83% felt very ready for implementation. Students, particularly in higher grades, showed positive responses, with 80-100% finding the training excellent and feeling prepared for the application. Limitations: The limitations include varying levels of readiness among students and the need for additional support for some. Some students expressed neutrality or lesser readiness, especially in lower grades. Contribution: The initiative contributes to education technology integration, ensuring efficient and effective implementation of the mobile-based attendance system. The application benefits both teachers and students in improving attendance accuracy, saving time, and supporting academic success. The successful implementation sets a precedent for similar educational institutions and contributes to broader discussions on technology adoption in education.